1975
DOI: 10.1017/s007418090001069x
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Double System Containing the X-Ray Pulsar Her X-1

Abstract: A model for the double system with the X-ray source Her X-1 is considered. It is supposed that the central star has a sufficiently strong magnetic field for the outflow of the matter to occur in jets. When the neutron star is in the jet the optical depth τx attributable to the X-ray emission due to Compton scattering is greater than unity and the solid angle of the emitted X-radiation is broad, ∼ 180°. In the opposite case, τx < 1, there is a narrow angle of emission and the radiation falls on to the star a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 0 publications
7
72
0
Order By: Relevance
“…11 by dots with error bars associated with uncertainty in thermal insulating envelope composition; data are taken from Gusakov, Chugunov & Kantor 2014b;Chugunov, Gusakov & Kantor 2017) reveal the inadequacy of the standard model: additional dissipation of r-modes is required to stabilize many observed NSs [i.e., all NSs in the white region of 11(a)]. Chugunov et al (2017) analyze the formation of MSPs via the recycling scenario (Bisnovatyi-Kogan & Komberg 1976;Alpar et al 1982;Bhattacharya & van den Heuvel 1991;Papitto et al 2013) and suggest 'minimal' constraints to the instability windows, which allow them to explain the observations of transiently accreting neutron stars, and the formation of high-frequency MSPs, simultaneously. The corresponding 'minimally constrained' instability window is shown in Fig.…”
Section: Upper Limit For Surface Temperature Of Msp 47 Tuc Aa and Conmentioning
confidence: 99%
“…11 by dots with error bars associated with uncertainty in thermal insulating envelope composition; data are taken from Gusakov, Chugunov & Kantor 2014b;Chugunov, Gusakov & Kantor 2017) reveal the inadequacy of the standard model: additional dissipation of r-modes is required to stabilize many observed NSs [i.e., all NSs in the white region of 11(a)]. Chugunov et al (2017) analyze the formation of MSPs via the recycling scenario (Bisnovatyi-Kogan & Komberg 1976;Alpar et al 1982;Bhattacharya & van den Heuvel 1991;Papitto et al 2013) and suggest 'minimal' constraints to the instability windows, which allow them to explain the observations of transiently accreting neutron stars, and the formation of high-frequency MSPs, simultaneously. The corresponding 'minimally constrained' instability window is shown in Fig.…”
Section: Upper Limit For Surface Temperature Of Msp 47 Tuc Aa and Conmentioning
confidence: 99%
“…Bisnovatyi-Kogan & Komberg (1974) suggested that pulsars in binaries may have low magnetic Ðelds because of this e †ect. Romani (1990Romani ( , 1995 outlined a picture in which matter initially accretes onto the polar cap, eventually spreads under the weight of the accumulated matter, and advects the magnetic Ðeld inward.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of radio pulsars in close binaries, in spite of intensive searches could be explained by the only reason: during accretion stage the magnetic field of the neutron star is screened by the inflowing accreting gas, so the recycled pulsar should have B ∼ 10 8 − 10 10 G, 2-4 orders of magnitude smaller than average field strength of radio pulsars. Discovery of the first binary pulsar [41], and subsequent discovery of more than 100 recycled pulsars [51,56] had confirmed this conclusion: all recycled pulsars have small values of magnetic fields, as was predicted in [20].…”
Section: Recycled Radio Pulsarsmentioning
confidence: 62%
“…Magnetic fields of radio pulsars estimated using (2.1) with observational values of P andṖ lay in a wide region between 10 8 and 10 13 G [55]. There are two distinctly different groups: single radio pulsars with periods exceeding 0.033 sec, and magnetic fields between 10 11 and 10 13 G, and recycled pulsars (RP), present or former members of close binary systems with millisecond periods and low magnetic fields between 10 8 and 10 10 G. Low magnetic field of recycled pulsars is probably a result of its damping during preceding accretion stage [20,22]. Lines of constant magnetic field (dashed), characteristic age (dash-dotted) and spin-down energy loss rate (dotted) are also shown.…”
Section: Radio Pulsarsmentioning
confidence: 99%
See 1 more Smart Citation